Reabilitação de vigas de concreto armado em escala real com reforço à flexão com laminados de CFRP passivos e protendidos - Pereira, Marcelo Fernandes (2024)
Among the possible methods of structural strengthening which can be highlighted are: the section enlargement, reinforcement with composite materials, metallic profiles, use of metal plates, and external prestressing. Of these mentioned methods, the use of Fiber Reinforced Polymers (FRP) stands out due to their quick and practical application and good mechanical properties. The effectiveness and structural performance of the use of FRP laminates, and/or sheets, in passive flexural strengthening systems of reinforced concrete elements has been proven by different studies. In passive FRP strengthening systems, the failure modes of the elements are commonly characterized by the detachment of the strengthening material under loads corresponding to only 20 to 50% of the ultimate capacity of the FRP. To improve the use of the FRP systems based on externally bonded materials, different studies have analyzed the behavior of structures with prestressed FRP laminates over the past decade. These studies indicate greater increases in the load-carrying of strengthened elements and higher utilization levels in the strengthening material compared to the passive bonding technique. In this context, the present work aims to analyze, through an experimental program, the mechanical behavior of full-scale reinforced concrete beams, either pre-cracked or not, flexurally strengthened with prestressed and passive CFRP laminates. The work also proposes and evaluates design models with the experimental obtained results. For this purpose, an experimental program was carried out with five reinforced concrete beams subjected to four-point bending tests until failure, one unstrengthened beam (reference), two beams flexurally strengthened with externally bonded passive CFRP laminates, and two beams flexurally strengthened with externally bonded prestressed CFRP laminates. One beam of each trengthening type was subjected to pre-cracking. The results showed that the passive strengthening increased the yielding load of up to 16.9% compared to the unstrengthened beam. An increase of up to 23.3% was observed at the ultimate load compared to the reference beam. The use of prestressed strengthening promoted an increase of up to 37.9% and 41.9% in the loads at the yielding of the steel reinforcement and at the ultimate load, respectively, compared to the reference beam. The use of prestressed laminate is more effective to increase the loadcarrying of the elements. Regarding the strains in the strengthening material, considering that the CFRP laminate showed an estimated maximum strain of approximately 14.61‰, an effectiveness of up to 44.4% and 68.4% was obtained for passive and prestressed strengthening, respectively. Thus, the ability of the prestressed strengthening system to attain higher strain levels for the strengthening material compared to passive strengthening is highlighted. Furthermore, the ability of the prestressed CFRP laminate strengthening system to reduce vertical displacements and pre-existing crack openings in structural elements was verified. The simplified analytical model herein proposed for determining the load-bearing capacity of reinforced concrete elements flexurally strengthened with prestressed CFRP laminates proved to be effective for estimating the load-carrying capacity of beams subject to flexure. However, it is important to highlight the need for the correct definition of the strain to be attributed to the strengthening material in determining the ultimate resistant moment of the cross-section.